Genomewide Histone H3 Lysine 9 Acetylation Profiling in CD4+ T Cells Revealed Endoplasmic Reticulum Stress Deficiency in Patients with Acute‐on‐chronic Liver Failure. (November 2015) - Jin, L.; Wang, K.; Liu, H.; Chen, T.; Yang, Y.; Ma, X.; Wang, J.; Li, Y.; Du, D.; Zhao, Y.; He, Y.
Abstract Acute‐on‐chronic liver failure (ACLF) displayed 'sepsis‐like' immune paralysis. Little is known about the role of CD4+ T lymphocytes, the primary regulator of innate and adopted immune system, played in ACLF. Acetylation of histone H3 lysine 9 (H3K9ac), a key epigenetic modification, tightly controls gene transcription. Whether and how does H3K9ac modification regulate CD4+ T cells in ACLF remains unclear. PBMCs were isolated from patients with ACLF, immune tolerance of chronic hepatitis B (CHB‐T) and immune active of chronic hepatitis B (CHB‐A). Then, CD4+ T lymphocytes were purified by magnetic microbeads, and the purity was confirmed by flow cytometry. H3K9ac variations were analysed in CD4+ T cells using chromatin immunoprecipitation microarray and then confirmed by quantitative PCR. Whole‐genome H3K9 acetylation analyses were conducted by bioinformatics. A total of 70 genes were differently modified in H3K9ac between CHB‐A and ACLF groups, while 44 genes were differently modified in H3K9ac between CHB‐T and ACLF groups. Clustering algorithm analysis showed patients with ACLF displayed 'sepsis‐like' immune paralysis. Functional analysis showed endoplasmic reticulum (ER) stress, or downstream pathway‐related genes, such as BIP, ATF4, PER1, CSNK1D, IRF3, BNIP1, AKT1 and UBC, were differentially modified in ACLF. We profiled H3K9 acetyl modification in CD4+ T lymphocytes from HBV‐infected patients with three different immune states, that is ACLF, immune tolerance and immune active phases. ACLF displayed 'sepsis‐like' immune paralysis. ER stress in CD4+ T lymphocytes attributed to ACLF. This study provides some useful clues for revealing the mechanisms underlying ACLF.